Fat-free mass index in a diverse sample of female collegiate athletes - Harty, P. S.; Zabriskie, H. A.; Stecker, R. A.; Currier, B. S.; Moon, J. M.; Jagim, A. R.; Kerksick, C. M. (International Journal of Exercise Science Conference Proceedings, 2019)
Fat-free mass index (FFMI) is a height-adjusted metric of fat-free mass that has been suggested to have a variety of applications in the classification of athletic populations, including the assessment of athletic potential and capacity for further fat-free mass accretion. Previous researchers have identified FFMI upper limits of 28.1 kg/m2 in male football players and 25 kg/m2 in resistance-trained males. However, little information exists regarding normative FFMI values and upper limits of FFMI in female athletes. PURPOSE: The purpose of this study was to determine sport-specific FFMI values and the natural upper limit of FFMI in female athletes. METHODS: 372 female collegiate athletes (Mean ± SD; Age: 20.0 ± 1.6 years, Height: 167.6 ± 7.5 cm, Weight: 69.5 ± 13.0 kg, Percent body fat: 24.2 ± 5.5 %) underwent body composition assessment via dual-energy x-ray absorptiometry. FFMI was calculated by dividing fat-free mass by height squared and was adjusted to mean height via linear regression. Between-sport differences were identified using one-way ANOVA with Tukey post-hoc tests. RESULTS: Height-adjusted and unadjusted FFMI values were not significantly different (p < 0.05). Thus, unadjusted data was used to report all results (Table 1). Average FFMI was 18.82 ± 2.09 kg/m2. FFMI in rugby athletes was significantly higher (p < 0.05) than in gymnastics, ice hockey, lacrosse, swim & dive, and volleyball. FFMI in cross country and synchronized swimming was significantly lower (p < 0.05) than in Olympic weightlifting, wrestling, and rugby. The upper limit for FFMI in female athletes (97.5th percentile) was 23.9 kg/m2. The upper limit for rugby athletes in this sample was 25.78 kg/m2. CONCLUSION: This study is the first to report upper limits for FFMI in female collegiate athletes and more than doubled the available normative FFMI data in female athletes. These results can be used to guide personnel decisions and assist with body composition, training, and nutritional goals.